New Delivery Systems and Propellants - Myrna Dolovich (Canadian Respiratory Journal)
The removal of chlorofluorocarbon (CFC) propellants from industrial and household products has been agreed to by over 165 countires of which more than 135 are developing countries. The timetable for this process is outlined in the Montreal Protocol on Substances that Deplete the Ozone Layer document and in several subsequent amendments. Pressured metered dose inhalers (pMDIs) for medical use have been granted temporary exemptions until replacement formulations, providing the same medication via the same route, and with the same efficacy and safety profiles, are approved for human use. Hydrofluoroalkanes (HFAs) are the alternative propellants for CFCs-12 and -114. Their potential for damage to the ozone layer is nonexistent, and while they are greenhouse gases, their global warming potential is a fraction (one-tenth) of that of CFCs. Replacement formulations for almost all inhalant respiratory medications have been or are being produced and tested; in Canada, it is anticipated that the transition to these HFA or CFC-free pMDIs will be complete by the year 2005. Initially, an HFA pMDI was to be equivalent to the CFC pMDI being replaced, in terms of aerosol properties and effective clinical dose. However, this will not necessarily be the situation, particularly for some corticosteroid products. Currently, only one CFC-free formulation is available in Canada – Airomir, a HFA salbutamol pMDI. This paper discusses the in vitro aerosol characteristics, in vivo deposition and clinical data for several HFA pMDIs for which there are data available in the literature. Alternative delivery systems to the pMDI, namely, dry powder inhalers and nebulizers, are briefly reviewed.